The Shadow Economy in Pakistan: An Analysis with MIMIC Model - Jabbar, Attiqa; Iqbal, Javed (Pakistan Journal of Humanities and Social Sciences, 2021)
This paper explicitly presents the estimation of the size and development of the shadow economy. The study examines the impact of multiple exogenous causes (observed variables) on the shadow economy (latent variable) and the size of the shadow economy influencing the performance of multiple macroeconomic indicators. In order to accomplish this econometric analysis, a MIMIC Model (Multiple Indicators Multiple Causes Model) is applied over the period 2011 to 2021. The results indicate that the tax burden, business freedom, unemployment rate, and Gross Domestic Product are the key driving forces of the shadow economy in Pakistan. The findings are potentially beneficial for the policymakers in identifying and dealing with the shadow economic activities as well as developing the strategies relevant to the economic policy.